1998
DOI: 10.1136/ip.4.3.181
|View full text |Cite
|
Sign up to set email alerts
|

Seating positions and children's risk of dying in motor vehicle crashes

Abstract: Parents and others who transport children should be strongly encouraged to place infants and children in rear seats whether or not vehicles have airbags. Existing laws requiring restraint use by children should be strengthened and actively enforced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
2
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(66 citation statements)
references
References 20 publications
(11 reference statements)
3
59
2
2
Order By: Relevance
“…[5][6][7][8]10 Those studies all found unrestrained children (particularly those in the front seat) to be at the greatest risk of injury. The results from our multivariate analyses extend those of prior studies by providing additional details on the effects of age-appropriate restraint (not available in other national sources of crash data) and by examining the relative benefits of appropriate restraint and seating position for relevant age groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8]10 Those studies all found unrestrained children (particularly those in the front seat) to be at the greatest risk of injury. The results from our multivariate analyses extend those of prior studies by providing additional details on the effects of age-appropriate restraint (not available in other national sources of crash data) and by examining the relative benefits of appropriate restraint and seating position for relevant age groups.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] Although most studies reported that restraint use in rear seats offers the greatest protection to children of any age, Braver et al 8 showed that older children with optimal restraint in the front seat were at lower risk of injury than were unrestrained children in the rear. In addition, the previous studies either did not contain sufficient detail for determination of the ageappropriateness of restraint use [5][6][7][8]10 or did not examine the benefits of appropriate restraint and seating position across a wide range of child ages 9,12 or crash types. 11 Information on the relative benefits of rear seating and appropriate restraint would assist policymakers faced with choices regarding provisions for rear seating or age-appropriate restraint when considering enhancements to state child restraint laws.…”
mentioning
confidence: 99%
“…2,[12][13][14] Unfortunately, most existing motor vehicle legislation addresses only restraint use for children in the front seats; it does not address either child restraint in the rear seats or seating position. 15 Rhode Island's legislation seems to have contributed to changing child seating behavior in motor vehicles.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Nationwide educational campaigns now emphasize the need for children to be properly restrained and seated in the rear seats, and professional organizations and government agencies have endorsed these safety messages. The National Transportation Safety Board issued a recommendation in 1997 that each state amend its child passenger safety laws to make it compulsory for children to ride in the rear seats.…”
mentioning
confidence: 99%
“…Anne ve babaların en önemli görevlerinden birisi de, bu kazalarda bebek ve çocuklarının zarar görmesini önlemek veya en aza indirmek için, güvenlik önlemlerini arttırmaktır. Bunun için alınacak önlemlerin başında, otomobillerde seyahat esnasında çocuk oto güven-lik koltuğu (ÇOGK) kullanımı ve emniyet kemeri bağlanması gelmektedir (2,3).…”
Section: Introductionunclassified